Automatic Control of the 30 MWe SEGS VI Parabolic Trough Plant - Stuetzle, Thorsten A. (University of Wisconsin-Madison, 2002)
A solar electric generating system (SEGS) can be divided into two major subsystems (Lippke, 1995): a solar collector field and a conventional Clausius-Rankine cycle with a turbine-generator. For the 30 MWe SEGS VI Parabolic Trough Collector Plant, one task of a skilled plant operator is to maintain a specified set point of the collector outlet temperature by adjusting the volume flow rate of the heat transfer fluid circulating through the collectors. The collector outlet temperature is mainly affected by changes in the sun intensity, by the collector inlet temperature and by the volume flow rate of the heat transfer fluid. For the development of next generation SEGS plants and in order to obtain a control algorithm that approximates an operator's behaviour, a linear model predictive controller is developed for use in a plant model. The plant model, which is discussed first in this work, consists of a model for the parabolic trough collector field and a model for the power plant. The plant model's usefulness is evaluated through a comparison between predicted and measured data. The performance of the controller is evaluated on four different days in 1998. The influence of the control on the gross output of the plant is examined as well.
Under the supervision of Professors William A. Beckman and John W. Mitchell; 163pp.
Keywords: Thesis (M.S.)--University of Wisconsin--Madison, 2002.; Dissertations Academic Mechanical Engineering.; University of Wisconsin--Madison. College of Engineering.